Keragaan Beberapa Galur Harapan Kacang Tanah pada Lahan Kering Masam di Sumatera Barat - Atman Atman (Jurnal Penelitian Pertanian Terapan, 2012)
In West Sumatra Province, peanut represent one of the priority commodity in development of food crop subsector. But, till now, acceleration production less is seething with excitement to have, fluctuation, and tend to down hilly. To overcome this problems, can be conducted by planting pre-eminent varieties newly peanut have lenient and high result potency to at dry acid dry soil as farm which still available to extension of agriculture areal. This research aim to get peanut promising lines which capable to adapt in dry acid soil, with pH <5. Research have been executed on farmer land of district of Talawi Town of Sawahlunto, West Sumatra, start September until December 2010 at dry acid soil (pH 4,57). Using 15 promising lines from Balitkabi Malang. that is: (1) GHM-2010-1; (2) GHM-2010-2; (3) GHM-2010-6; (4) GHM-2010-9; (5) GHM-2010-10; (6) GHM-2010-11; (7) GHM-2010-15; (8) GHM-2010-17; (9) GHM-2010-19; (10) GHM-2010-52; (11) GHM-2010-56; (12) GHM-2010-57; (13) GHM-2010-58; (14) GHM-2010-67; and (15) GHM-2010-71. Land processed perfectly of the size map each 4x6 m. Distance plant 40x15 cm, counted two seed per hole. Manure given by counted 50 kg Urea + 100 kg SP36 + 50 kg KCl per hectare. Result of research indicate that treatment of peanut promising lines give real influence to plant height, number of pods per plant, number of seed per plant, percentage of fully pods, wet pods yield, and dry pods yield. While to number of branches per plant, heavy of wet crop, and heavy of dry crop do not significant. Chosen four peanut promising lines (GHM-2010-67, GHM-2010-10, GHM-2010-11; and GHM-2010-9) are capable to give result of dry pods yield successively 2,92 ton.ha-1 ; 2,82 ton.ha-1 ; 2,63 ton.ha-1 ; and 2,26 ton.ha-1 at dry acid soil in Sawahlunto with degree of acidity of land (pH) <5. Keywords: peanut, dry acid soil, Peanut New Strains